Mobile Learning: Transforming the Delivery of Education and Training - Mohamed Ally (Athabasca University Press, 2009)
This collection is for anyone interested in the use of mobile technology for various distance learning applications. Readers will discover how to design learning materials for delivery on mobile technology and become familiar with the best practices of other educators, trainers, and researchers in the field, as well as the most recent initiatives in mobile learning research. Businesses and governments can learn how to deliver timely information to staff using mobile devices. Professors can use this book as a textbook for courses on distance education, mobile learning, and educational technology.